Biofilm Community Diversity after Exposure to 0.4% Stannous Fluoride Gels - Reilly, Cavan (J Appl Microbiol, 2014)
AIMS: To test the effect of %0.4 stannous fluoride (SnF(2)) glycerin based gels on the bacterial ecology in both a clinical observational study and in vitro polymicobial biofilm model. METHODS AND RESULTS: The influence of stannous fluoride (0.4% SnF(2)) gels on bacteria was tested in both an observational study in children 6-12 years of age (n=20) and an in vitro biofilm model system. The plaque derived multi-species bacterial biofilm model was based on clinical bacterial strains derived directly from the clinical study. Potential changes in the plaque ecology were determined through the Human Oral Microbial Identification Microarray-HOMIM (n=10). The semiquantitative data resulting from this system were analyzed with cumulative logit models for each bacterial strain and Bonferroni adjustments were employed to correct for multiple hypothesis testing. Both hierarchical biclustering and principal components analysis were used to graphically assess reproducibility within subjects over time. Mixed effects models were used to examine changes in plaque scores and numbers of bacterial strains found in the various conditions. CONCLUSIONS: Both the observational clinical study and the biofilm model showed that short-term use of 0.4% SnF(2) gel has little effect on the bacterial plaque ecology. The amount of plaque accumulation on a subject's teeth, which was measured by plaque index scores failed to show statistical significant changes over the two baselines or after treatment (p=0.9928). The in vitro results were similar when examining the effect of 0.4% SnF(2) gels on biofilm adherence through a crystal violet assay (p= 0.1157). SIGNIFICANCE AND IMPACT OF THE STUDY: The bacteria within the dental biofilms showed resilience in maintaining the overall community diversity after exposure to 0.4% Stannous Fluoride Gels. The study supports that the immediate benefits of using these gels each night to manage caries in children may be strictly from fluoride ions inhibiting tooth demineralization.